Measuring system for control of kinematic parameters of continuous horizontal casting - E. I. Marukovich; Ju. L. Stanjulenis; V. V. Chubuk; V. A. Zemtsov (Литьë и металлургия)
The report describes the computer aided measuring system allowing to define optimal pressing effort of pulling stand rolls depending on the casting drawing force.